2000
DOI: 10.1247/csf.25.187
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Effects of Hydrogen Peroxide on Cytosolic Ca2+ Homeostasis in Rat Pancreatic .BETA.-cells.

Abstract: ABSTRACT. Oxygen-free radicals are thought to be a major cause of b-cell dysfunction in diabetic animals induced by alloxan or streptozotocin. We evaluated the effect of H2O2 on cytosolic Ca 2+ concentration ([Ca 2+ ]i) and the activity of ATP-sensitive potassium (K + ATP) channels in isolated rat pancreatic b-cells using microfluorometry and patch clamp techniques. Exposure to 0.1 mM H2O2 in the presence of 2.8 mM glucose increased [Ca 2+ ]i from 114.3±15.4 nM to 531.1±71.9 nM (n=6) and also increased frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 50 publications
2
20
2
1
Order By: Relevance
“…We demonstrated that the modest increase in [Ca2+]i observed after H202 treatment (the first phase) is due to an increased permeability of the thapsigargin-sensitive intracellular Ca2+ stores [24]. The second phase of [Ca2+]i elevation has been suggested to be due to the in- creased Ca2+ permeability of the plasma membrane [24], or alternatively it has been speculated that it is induced by an increased influx of Ca2+ through the non-selective cation channel activated by H2O2 treatment [16] . Our results revealed a remarkable increase in [Ca2+]; after 20 min of exposure to 0.3 mM H2O2 (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We demonstrated that the modest increase in [Ca2+]i observed after H202 treatment (the first phase) is due to an increased permeability of the thapsigargin-sensitive intracellular Ca2+ stores [24]. The second phase of [Ca2+]i elevation has been suggested to be due to the in- creased Ca2+ permeability of the plasma membrane [24], or alternatively it has been speculated that it is induced by an increased influx of Ca2+ through the non-selective cation channel activated by H2O2 treatment [16] . Our results revealed a remarkable increase in [Ca2+]; after 20 min of exposure to 0.3 mM H2O2 (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The first-phase increase in [Ca2+]; is induced by the reduction of cytosolic ATP levels caused by mitochondrial dysfunction after the H202 treatment and the failure of Ca2+-pumping into the endoplasmic reticulum [17]. We demonstrated that the modest increase in [Ca2+]i observed after H202 treatment (the first phase) is due to an increased permeability of the thapsigargin-sensitive intracellular Ca2+ stores [24]. The second phase of [Ca2+]i elevation has been suggested to be due to the in- creased Ca2+ permeability of the plasma membrane [24], or alternatively it has been speculated that it is induced by an increased influx of Ca2+ through the non-selective cation channel activated by H2O2 treatment [16] .…”
Section: Discussionmentioning
confidence: 91%
“…In studies on rat beta cells using hydrogen peroxide it was shown that hydrogen peroxide induced rapid increases in Ca 2+ depending on mobilzation of Ca 2+ both from intracellular and extracellular compartments. This was accompanied by an increased frequency of K ATP channel openings, an effect interpreted to depend on a metabolic inhibition induced by the free radical and not a direct effect on the K ATP channels of the beta cells [13,14]. In another study aqueous NO was applied to rat islet cells which led to a rapid and transient increase in intracellular Ca 2+ concentrations probably via a mobilization of Ca 2+ from the endoplasmic reticulum [15].…”
Section: :80-88]mentioning
confidence: 98%
“…16) In our previous study in INS-1 β-cells, we showed that H 2 O 2 -induced apoptosis was abolished by 1,2-bis(2-aminophenoxy) ethane-N,N,N′,N′-tetraacetic acid-acetoxymethyl ester (BAPTA/AM), a chelator of intracellular Ca 2+ ; by 2-aminoethoxydiphenylborate (2-APB), a blocker of inositol 1,4,5-trisphosphate (IP 3 ) receptors and cation channels, including SOCs; and by xestospongin D, a blocker of IP 3 receptors and was partially blocked by SKF-96365, a blocker of nonselective cation channels, including SOCs. 17 ), BAPTA/AM, fura-PE3-acetoxymethyl ester (fura-PE3/AM), cremophor EL, carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP), and the goat anti-mouse immunoglobulin G (IgG) horseradish peroxidase (HRP) antibody were from Sigma-Aldrich (St. Louis, MO, U.S.A.).…”
mentioning
confidence: 99%